Variation of cultivated mungbean and wild vigna as revealed by random amplified polymorphic DNA markers - S. V., Kumar; T. M., Saw; Tan, Soon Guan; S. C., Quah (Universiti Putra Malaysia Press, 2003)
The genetic variation of nine varieties of cultivated mungbean (Vigna radiata) and three local populations of wild Vigna (V. trinervia) were evaluated in this study using RAPD markers. A total of 65 scorable DNA fragments ranging in size from 173-1,500 bp were obtained from the PCR amplification usingfive RAPD primers of which 95.38% were polymorphic. Cluster analysis revealed two major groups in which the first group consists of the nine varieties ofV. radiata, while the second group includes the three populations ofV. trinervia. This information is useful for plant breeders to make informed decisions in an effort to devise breeding or crossbreeding programmes for the development of the crop.